Interest Rate Theory in Islamic Economic Perspective - Robist Hidayat (Basic and Applied Accounting Research Journal, 2021)
Inflation is a condition in which there is a sharp (absolute) increase in prices that lasts continuously for a long period of time followed by a decline in the real (intrinsic) value of a country's currency. circulating through an increase in bank interest rates. For this reason, the government carries out monetary policy by suppressing the money supply through increasing bank interest rates. However, the interest rate has various kinds, namely classical interest rate theory, neo classical, modern keyness and hicks. Therefore, this study focuses more on interest rates and the theory of interest rates by experts. So that it produces descriptive research.